Implementation Of Problem-Based Learning: An Effort To Improve Mathematics Learning Achievement Of Jatinom Elementary School Students, Klaten District, Indonesia - Sulasmi Sulasmi (Universitas Sebelas Maret, 2022)
The aim of this research is to improve students' mathematics learning outcomes through the application of the Problem Based Learning learning model. This research was conducted at Jatinom State Elementary School, Klaten Regency, Indonesia in the 2022-2023 academic year. The subjects of this research were 20 fourth grade students at SD Negeri Jatinom, Klaten Regency, Indonesia. The research method applied is classroom action research, a type of individual action research. The instrument used is a multiple choice written test. Research data was collected through student learning outcomes tests in each cycle I and II. Data analysis techniques are carried out using descriptive methods to determine the mean, median, mode, present class intervals and present them in tables. The results of this research show that: 1) The application of the Problem Based Learning learning model in cycle I achieved an average student learning outcome score of 72.86. 2) The application of the Problem Based Learning learning model in cycle II experienced an increase with an average value of 97.56. 3) Implementation of the Problem Based Learning learning model can increase student learning outcomes from cycle I to cycle II by 45.24% with a pass percentage of 100%. Thus, it can be concluded that the application of the Problem Based Learning model can improve the mathematics learning outcomes of class IV at SD Negeri Jatinom, Klaten Regency, Indonesia.